ARAH KEBIJAKAN HUKUM (LEGAL POLICY) KETENAGAKERJAAN BARU PASCA PUTUSAN MAHKAMAH KONSTITUSI NO. 168/PUU-XXI/2023: DARI INKONSISTENSI NORMA MENUJU KEADILAN SOSIAL - Yosep Ubaama Kolin; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Historically, labor law policy in Indonesia has exhibited acute normative inconsistency, driven by the persistent tension between safeguarding workers' welfare and accommodating investment demands. This inconsistency culminated in the enactment of Law No. 6 of 2023 on Job Creation, which adopted a flexible labor market approach, thereby triggering the commodification of labor and a serious constitutional crisis. The issuance of the Constitutional Court Decision Number 168/PUU-XXI/2023 serves as a landmark piece of creative jurisprudence and a constitutional "emergency brake," mandating the formulation of a new, independent labor law (standalone law) within a maximum period of two years. This paper aims to analyze the root causes of normative inconsistency in labor law and formulate a new, social justice-based legal policy framework in the post-decision era. Utilizing a normative legal research method guided by Nonet-Selznick and Mahfud MD’s Theory of Legal Product Character, John Rawls’s Theory of Distributive Justice, and the social justice principle of Pancasila, this study reveals two fundamental findings. First, the systemic normative inconsistency stems from the deconstruction of labor rights for short-term economic pragmatism and the profound absence of meaningful public participation, which ultimately yielded an orthodox-conservative legal product. Second, the new legal policy must undertake a formal reconstruction by operating strictly outside the omnibus law framework through a deliberative tripartite dialogue, alongside a substantive reconstruction rooted in social justice. This substantive blueprint must restore wage distribution based on the Real Decent Living Needs (KHL), strictly restrict the outsourcing system, and tighten the requirements for employment termination. Through this comprehensive restructuring, the national labor law architecture is directed toward a balanced flexicurity model, ensuring that economic dynamics operate in tandem with the preservation of workers' human dignity.